2020
DOI: 10.1002/etc.4899
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanesulfonic Acid–Induced Toxicity on Zebrafish Embryos in the Presence or Absence of the Chorion

Abstract: Perfluorooctanesulfonic acid (PFOS) is a perfluorinated compound used in many industrial and consumer products. It has been linked to a broad range of adverse effects in several species, including zebrafish (Danio rerio). The zebrafish embryo is a widely used vertebrate model to elucidate potential adverse effects of chemicals because it is amenable to medium and high throughput. However, there is limited research on the full extent of the impact the chorion has on those effects. Results from the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…Preliminary results found no significant effects on survival or reproduction of zebrafish at the highest tested PFOS concentration of 100 000 ng/L. Reduced growth was observed at the highest PFOS exposure concentration of 100 000 ng/L (Gust et al, 2021; Moore et al, 2022), but the growth reduction reported by Keiter et al (2012) at 600 ng/L was not reproducible. The USEPA (2022b) discussed Keiter et al (2012) but did not include the study results in the quantitative derivation of the draft national recommended aquatic life criteria for PFOS due to the “…poor concentration‐response relationship with the endpoints evaluated…” and test design complications.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Preliminary results found no significant effects on survival or reproduction of zebrafish at the highest tested PFOS concentration of 100 000 ng/L. Reduced growth was observed at the highest PFOS exposure concentration of 100 000 ng/L (Gust et al, 2021; Moore et al, 2022), but the growth reduction reported by Keiter et al (2012) at 600 ng/L was not reproducible. The USEPA (2022b) discussed Keiter et al (2012) but did not include the study results in the quantitative derivation of the draft national recommended aquatic life criteria for PFOS due to the “…poor concentration‐response relationship with the endpoints evaluated…” and test design complications.…”
Section: Discussionmentioning
confidence: 92%
“…For PFOS alone, Zodrow et al (2021) identified 187 aquatic toxicity endpoints from 60 papers with approximately 60% of the papers published after 2007. It should be noted that, as new studies and data are generated, emphasis should be placed on the evaluation of study design, QA/QC, and analytical methodologies to ensure only well‐founded studies are used for criteria development (Moore et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial variation in the effective PFOS concentrations causing significant lethal effects in zebrafish can be observed across previous studies. For example, in zebrafish embryo exposures lasting between 2 and 6 dpf, LC50 values for PFOS exposures ranged from 2200 to 68 000 µg/L (Huang et al, 2021; Krupa et al, 2022; Shi et al, 2008; Ulhaq et al, 2013; Vogs et al, 2019; Wasel et al, 2022; Zheng et al, 2012), the LOECs ranged from 3200 to 10 000 µg/L (Martinez et al, 2019; Ortiz‐Villanueva et al, 2018; Truong et al, 2014), whereas the no‐observed‐effect concentrations (NOECs) ranged from 1530 to 20 000 µg/L (Huang et al, 2021; Mylroie et al, 2021). Survivorship responses to PFOS exposures extending beyond the embryonic life stage into subchronic and chronic exposures include reporting of a 30‐dpf LC50 of 490 µg/L (Krupa et al, 2022), while Guo et al (2019) and Bao et al (2019) reported 21‐dpf NOECs of 80 and 200 µg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type AB strain adult zebrafish (Zebrafish International Resource Center) used to generate the parental (P) generation was maintained as described in Mylroie et al (2021). The P generation was bred in an iSpawn (Tecniplast) breeding chamber using 58 males and 30 females as parents; spawning occurred for 30 min initiated by the start of the daily light cycle.…”
Section: Zebrafish Embryo Production For Pfos Exposurementioning
confidence: 99%
“…Alongside studies of apparent bioaccumulation, numerous toxicological studies utilizing fish have also connected PFOS exposure to toxicity and an array of adverse effects including altered reproductive function, developmental deformities, endocrine disruption, and hepatotoxicity (Hagenaars et al, 2008;Kang et al, 2019;Shi et al, 2008Shi et al, , 2009. With relevance to aquatic biota, a number of studies have investigated the toxicity of PFOS (and many other PFAS) in the zebrafish (Danio rerio), as an established laboratory model, and more specifically, early life (i.e., embryonic, larval) stages of this species (Huang et al, 2010;Krupa et al, 2022;Mylroie et al, 2021;Shi et al, 2008). These studies have indeed identified a range of potential toxicological endpoints, and notably, the zebrafish embryo model in particular has enabled studies that elucidate the role of developmental stage, and associated stagedependent mechanisms and targets.…”
Section: Introductionmentioning
confidence: 99%